Audit Internal terhadap Kecurangan dan Penyimpangan Keuangan Pemerintah Daerah - Simanjuntak, Tumpak Haposan (Universitas Batanghari Jambi, 2024)
This study examines the role of Internal Audit in strengthening local government financial resilience by integrating the concept of financial resilience from various sources. The research found that Internal Audit can contribute to responding to and overcoming financial stresses by improving the effectiveness of internal control, compliance, operational efficiency, and risk management. Internal Audit not only responds to financial pressures, but is also proactive in fraud prevention and financial risk management. The research method used a qualitative case study approach, the research involved 15 internal audit practitioners from various government institutions. The holistic involves in-depth interviews, document analysis, and direct observation to dive into the internal audit practices conducted by respondents. The results show that effective internal audit practices not only have an impact on fraud detection and prevention, but also play a crucial role in improving the integrity of financial reporting and accountability of local governments. However, some obstacles, such as budget, personnel, and technology constraints, may affect internal audit performance. Improvement recommendations include greater investment in technology training, better budget allocation, and increased number of personnel in internal audit.